Prediction and Verification of Epimedium Flavonoids With Different Glycosylation Numbers in Reversing Glucocorticoid-Induced Bone Formation Inhibition by Molecular Docking and Zebrafish - Jiang, Jun; Xiao, Jianpeng; He, Jinjin; Cai, Zhihui; Chen, Jianping; Yin, Jiangning (Frontiers in Environmental Science, 2022)
Glucocorticoids have been detected in environmental waters and their biological potency have raised concerns of their impact on aquatic vertebrates especially fish. Numerous researches showed the continuous and direct contact of aquatic vertebrates with glucocorticoid contaminants in environmental water will cause bone formation inhibition. The aim of this study is to predict and verify the effect of icaritin (IT), icaiiin (ICA) and baohuside-I (BHG-I) in reversing Glucocorticoid-induced bone formation inhibition (GIBFI) by molecular docking and zebrafish model. We contrasted their activity in reversing GIBFI from their affinity to bone metabolism proteins (OPG, RANKL, BMP-2, BMP-4 and Runx-2) by molecular docking. Subsequently, Zebrafish model was adopted to evaluate their reverse effects on GIBFI. Alizarin red staining coupled with image quantification were performed to evaluate the effects of IT, ICA and BHG-I on skeleton stained area (SSA) and cumulative optical density (COD). Inductively coupled plasma-mass spectrometry was applied to determinate the contents of bone mineral elements (CBME, Mg, K, Ca, Fe, Zn) in zebrafish bones. Docking results showed the receptors (BMP-2, BMP-4 and Runx2) all combined well to ICA, while BHG-I bound well to OPG, the affinity between IT and the above targets were the weakest. Fortunately, IT, ICA and BHG-I significantly increased the SSA, COD and the contents of Ca compared with the model group (p < 0.05) in the order of IT > ICA > BHG-I. In conclusion, the glycosyl groups increased the H-bond affinity between flavonoids and target sites, which weakened bone formation. IT, BHG-I and ICA all alleviated GIBFI, but their intensity order was IT > ICA > BHG-I.